The Algorithmic Spectator: Watching Annie Dorsen's Work. - Felton-Dansky, Miriam (TDR: The Drama Review (MIT Press))
Annie Dorsen's digital theatre works reshape the possibilities of the encounter between humans and algorithmic forces. They both address and embody a world in which emotion, cognition, and narrative are increasingly controlled by algorithmic programs; and they invite the spectator to confront a nonhuman and algorithmic logic experientially, altered and pressurized by the terms of the theatre itself.